High level of reduced glutathione contributes to detoxification of lipid peroxide‐derived reactive carbonyl species in transgenic Arabidopsis overexpressing glutathione reductase under aluminum stress. Issue 2 (23rd June 2017) - Yin, Lina; Mano, Jun'ichi; Tanaka, Kiyoshi; Wang, Shiwen; Zhang, Meijuan; Deng, Xiping; Zhang, Suiqi
Abstract : Lipid peroxide‐derived reactive carbonyl species (RCS), generated downstream of reactive oxygen species (ROS), are critical damage‐inducing species in plant aluminum (Al) toxicity. In mammals, RCS are scavenged primarily by glutathione (reduced form of glutathione, GSH), but in plant Al stress, contribution of GSH to RCS detoxification has not been evaluated. In this study, Arabidopsis plants overexpressing the gene AtGR1 (accession code At3g24170), encoding glutathione reductase (GR), were generated, and their performance under Al stress was examined. These transgenic plants (GR‐OE plants) showed higher GSH levels and GSH/GSSG (oxidized form of GSH) ratio, and an improved Al tolerance as they suffered less inhibition of root growth than wild‐type under Al stress. Exogenous application of 4‐hydroxy‐2‐nonenal, an RCS responsible for Al toxicity in roots, markedly inhibited root growth in wild‐type plants. GR‐OE plants suffered significantly smaller inhibition, indicating that the enhanced GSH level increased the capacity of RCS detoxification. The generation of H2 O2 due to Al stress in GR‐OE plants was lower by 26% than in wild‐type. Levels of various RCS, such as malondialdehyde, butyraldehyde, phenylacetaldehyde, (E)‐2‐heptenal and n‐octanal, were suppressed by more than 50%. These results indicate that high levels of GSH and GSH/GSSG ratio by GR overexpression contributed to the suppression of not only ROS, but also RCS. Thus, the maintenance of GSH level by overexpressing GR reinforces dual detoxification functions in plants and is an efficient approach to enhance Al tolerance.